Character in the Collection of Sixth Grader Stories - Rahmawati, Aenun; Helmanto, Fachri; Rosnawati (LADU: Journal of Languages and Education, 2024)
Background:  Character figure in short story refers to the traits, personalities, and attributes possessed by the characters in story short the. Character figure This form base for method reader understand and relate with story. Alif Integrated Islamic Elementary School implements a program to develop writing literacy for grade 6 students. This program takes the form of training in making Short Story anthology books. Literary works are description life humans created by the author. One of type literary works are story short. Purpose: The aim of this research is to identify characters in the collection short story student 6th grade SDIT ALIF Ciawi. Design and methods: Research methods used​ study This is analysis content, This method use ATLAS.ti For obtain data. Results: In research found that characters created by SDIT Alif Ciawi students two types were found character that is character anthropomorphic and non- anthropomorphic. Results of research conducted on 34 short stories SDIT Alif Ciawi students there is Non- Anthropomorphic characters namely "Human ", whereas character anthropomorphic emerges​ in short story student that is : Grasshopper, Eagle, Squirrel, Chameleon, Fish, Deer, Mother Birds, Cats, Rats, Ants, Snakes, Male Birds, Trees Petai, Broccoli, Vegetables, Apple Trees, Hap-hap, Jin Tomang, Durian Trees, Carrots, Spinach, Worms, Kriko and Mushrooms.